1992
DOI: 10.1083/jcb.119.6.1613
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of centrin: an EF-hand protein associated with three distinct contractile fibers in the basal body apparatus of Chlamydomonas.

Abstract: Abstract. Centrin, a 20-kD phosphoprotein with four calcium-binding EF-hands, is present in the centrosome/basal body apparatus of the green alga Chlamydomonas reinhardtii in three distinct locations: the nucleus-basal body connectors, the distal striated fibers, and the flagellar transition regions. In each location, centrin is found in fibrous structures that display calcium-mediated contraction. The mutant vfl2 has structural defects at all of these locations and is defective for basal body localization and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
108
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(111 citation statements)
references
References 32 publications
(75 reference statements)
2
108
0
1
Order By: Relevance
“…Yet both molecular and genetic analysis show that there is a single centrin gene (Huang et al, 1988). In the $2-220 mutant, a point mutation in the centrin gene leads to defective assembly of each of the three fibrous structures (Taillon et al, 1992;Taillon and Jarvik, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet both molecular and genetic analysis show that there is a single centrin gene (Huang et al, 1988). In the $2-220 mutant, a point mutation in the centrin gene leads to defective assembly of each of the three fibrous structures (Taillon et al, 1992;Taillon and Jarvik, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…2) could be due to the hetereogeneity of the ICLl components, and to the unusual richness in Gln and Pro residues of their N-termini. lar mass, isoelectric point, Ca2+-binding capacity), and their ability to form filamentous structures with Caz '-dependent contractile properties, previously suggested that these proteins might be centrins (Garreau de Loubresse et al, 1991), which also form contractile fibrous arrays in other protists such as ChZamydomonas (Salisbury et al, 1988;Taillon et al, 1992;Sanders and Salisbury, 1994).…”
Section: Infraciliary Lattice Polypeptides Are Recognized By Anticentmentioning
confidence: 99%
See 1 more Smart Citation
“…The bld2 mutation in the gene encoding -tubulin (Dutcher et al, 2002) and the uni3 mutation in the gene encoding ␦-tubulin (Dutcher and Trabuco, 1998) reveal the roles of these tubulins in assembly of B tubules and C tubules in triplet micro-tubules of the basal body wall. Mutations in the VFL1 gene encoding a basal body protein (Silflow et al, 2001) and in the VFL2 gene encoding centrin (Taillon et al, 1992) show the roles of these gene products in basal body positioning and segregation. Genomic and proteomic approaches have provided information on the protein composition of the flagella and basal bodies (Li et al, 2004;Keller et al, 2005;Pazour et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Centrin-based fiber contraction also plays an important role in flagellar excision in Chlamydomonas (21). Furthermore, green algal centrin is associated with the MTOC named the basal body in these organisms (22); however, the function of centrin at this location is not understood. Human cells contain two highly related centrin isogenes (8,9).…”
mentioning
confidence: 99%